2017
DOI: 10.1093/nar/gkx309
|View full text |Cite
|
Sign up to set email alerts
|

Cell-type-specific genome editing with a microRNA-responsive CRISPR–Cas9 switch

Abstract: The CRISPR–Cas9 system is a powerful genome-editing tool useful in a variety of biotechnology and biomedical applications. Here we developed a synthetic RNA-based, microRNA (miRNA)-responsive CRISPR–Cas9 system (miR-Cas9 switch) in which the genome editing activity of Cas9 can be modulated through endogenous miRNA signatures in mammalian cells. We created miR-Cas9 switches by using a miRNA-complementary sequence in the 5΄-UTR of mRNA encoding Streptococcus pyogenes Cas9. The miR-21-Cas9 or miR-302-Cas9 switche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
77
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 28 publications
0
77
0
1
Order By: Relevance
“…A subsequent study by Hirohide Saito's group expanded this approach to further miRNA candidates (miR-21 and miR-302a) (27). Moreover, they added a negative feedback loop to the system, thereby establishing a positive relation between miRNA abundance and Cas9 activity (27). To this end, the authors expressed Cas9 from an mRNA harbouring an L7Ae binding motif (K-turn), while co-expressing the L7Ae repressor from an mRNA carrying miRNA binding sites in its 3'UTR (27).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent study by Hirohide Saito's group expanded this approach to further miRNA candidates (miR-21 and miR-302a) (27). Moreover, they added a negative feedback loop to the system, thereby establishing a positive relation between miRNA abundance and Cas9 activity (27). To this end, the authors expressed Cas9 from an mRNA harbouring an L7Ae binding motif (K-turn), while co-expressing the L7Ae repressor from an mRNA carrying miRNA binding sites in its 3'UTR (27).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they added a negative feedback loop to the system, thereby establishing a positive relation between miRNA abundance and Cas9 activity (27). To this end, the authors expressed Cas9 from an mRNA harbouring an L7Ae binding motif (K-turn), while co-expressing the L7Ae repressor from an mRNA carrying miRNA binding sites in its 3'UTR (27). The resulting Cas-ON switch enabled miRNA-dependent Cas9 activation.…”
Section: Introductionmentioning
confidence: 99%
“…Hoffmann et al [106] developed a novel cell-type-specific Cas-ON switch based on AcrIIA4 and controlled by cellular miRNA signatures, confining spCas9 activity to hepatocytes or cardiomyocytes. In parallel with that work, Hirosawa et al constructed a synthetic mRNAdelivered Cas9-ON system using miRNA-responsive AcrIIA4 mRNA on the basis of improving the RNAbinding protein L7Ae-based miR-Cas9-ON switch they built previously [107,108]. Compared with a Cas-ON switch based on an L7Ae repressor, this Cas-ON switch design based on Acrs showed greater control than the previous system due to the high affinity of Acrs for Cas9-sgRNA complexes [106,107].…”
Section: Potential Application Of Type II Anti-crispr Proteinsmentioning
confidence: 99%
“…In parallel with that work, Hirosawa et al constructed a synthetic mRNAdelivered Cas9-ON system using miRNA-responsive AcrIIA4 mRNA on the basis of improving the RNAbinding protein L7Ae-based miR-Cas9-ON switch they built previously [107,108]. Compared with a Cas-ON switch based on an L7Ae repressor, this Cas-ON switch design based on Acrs showed greater control than the previous system due to the high affinity of Acrs for Cas9-sgRNA complexes [106,107]. Furthermore, a subsequent study validated the efficiency of this Cas-ON switch based on Acrs by adeno-associated virus vectors delivered to adult mice, and the data showed that NmeCas9, along with an AcrIIC3 constructed that was targeted for repression by liver-specific miR-122, allowed editing in the liver while repressing editing in heart muscle, indicating that this strategy provides safeguards against off-tissue genome editing [109].…”
Section: Potential Application Of Type II Anti-crispr Proteinsmentioning
confidence: 99%
“…Temporal control can be achieved by smallmolecule induction of gRNAs 14,15 or Cas9, 16 but this comes with limitations in terms of multiplexing and spatial control. Spatiotemporal control has been achieved by regulation of Cas9 via photoactivation 17 or via tissue-specific promoters 18,19 or microRNAs, 20 which comes with the unwelcome restriction that all gRNAs are subject to the same regulatory scope. Systematic mapping of the structure and sequence properties of functional gRNAs has revealed that Cas9 activity is tolerant to significant modifications the standard gRNA structure, 21,22 facilitiating introduction of auxiliary domains that enable conditional control of gRNA activity via structural changes induced by small-molecules, 23,24 protein-bound RNAs, 25 nucleases, 26 or nuclease-recruiting DNAs.…”
Section: Introductionmentioning
confidence: 99%